Putusnya Perkawinan dan Akibatnya dalam Hukum Islam dan Hukum Positif di Indonesia - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Ailsa Damara Putri; Novita Lailatul Ni’ma (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2024)
This study discusses the termination of marriage and its consequences in Fiqh Munakahat. The aim of this research is to examine and understand Fiqh Munakahat which discusses the termination of marriage and its consequences. The method used in this research is a qualitative method of literature review. Essentially, marriage is intended for lifelong happiness between a man and a woman. Divorce is granted if one party fails to fulfill its obligations adequately and the other party is unable to fulfill its obligations, leaving no option but to divorce. The results of this research conclude that the termination of marriage in Islamic law is that the divorce process such as talak, fasakh, or khul' must be regulated with full justice, decency, and caution. Both parties must obtain their rights fairly, including rights to property, maintenance, and child custody. The importance of maintaining family integrity and avoiding divorce except when absolutely necessary is emphasized in Islamic teachings. Furthermore, Islamic law emphasizes peaceful conflict resolution and settlement that respects the rights of all parties involved. By understanding the relevant principles of Islamic law and seeking guidance from qualified scholars and jurists, Muslims can handle the termination of marriage wisely, prioritizing mutual welfare, and upholding the moral values and ethics taught by Islam.